Purchase Intention of Secondhand Cosmetics Under the Influence of Attitude and Perceived Risk - Nur Latifah; Adelia Putri; Faisal Kamil; Ignatius Henry (Indonesian Business Review, 2022)
This research aims to disclose whether both attitudes and perceived risks such as economic value, product attributes, anxiety, and doubt were likely to influence consumer’s purchase intention regarding second-hand beauty products. Researchers carried out a quantitative method using survey questionnaires in order to collect data from respondents whom we have been selected before. Having statistically analyzed with SPSS, our study shed light on the most important factors in buying second-hand beauty products that are economic value and product attributes, positively. In addition, the risk factors such as doubt and anxiety of using this kind of product have a negative influence yet not significant. Our study suggests that there are some values for these businesses that should be emphasized for their marketing communication in an effort to capture more audiences.